A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMP MUHAMMADIYAH 1 PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS - Sari, Eka Putri; ', Erni; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This descriptive research was aimed to find out the ability of the second year students of SMP Muhammadiyah 1 Pekanbaru in comprehending descriptive texts. The research data were collected on March 2017. The subjects of this research were class VIII 2 consisted of 30 students. The data were collected by administering a test to the students in the form of multiple choice test. The framework of the test covered with six kinds of descriptive text and each text has five question items. The test contained 30 items. Based on the data analysis, it was found out that the highest score obtained by the students was in finding factual information with the mean score of 87.5 categorized into good to excellent level, and the lowest score was in finding inference with the mean score of 68 categorized into average to good level. As a conclusion, the ability of the second year students of comprehending descriptive texts was in the average to good level with the mean score of 77.4. The implication of the finding is that the students should increase their comprehension in order to reach excellent level.Keywords: Students’ ability, Descriptive texts